Can we improve the non-intrusive characterization of high-velocity air–water flows? Application of LIDAR technology to stepped spillways. Issue 2 (23rd February 2020) - Kramer, Matthias; Chanson, Hubert; Felder, Stefan
ABSTRACT: The characterization of high-velocity air–water flows is crucial for the design of hydraulic structures including stepped spillways. Recent experimental advances have shown that LIDAR technology can provide free-surface features in fully aerated flows at high spatial and temporal resolution. This manuscript presents the application of LIDAR to the aerated flows down a laboratory stepped spillway. While the LIDAR was not applicable in the clear water flow and the rapidly varied flow region, the results provided the most detailed spatial description of air–water surface features within the fully aerated flow towards the downstream end of the spillway. Good agreement was observed with characteristic air–water flow elevations and internal flow parameters. Integral time scales were obtained by means of correlation analyses and compared favourably with previous measurements. The present study highlighted the suitability of LIDAR in high-velocity air–water flows and the potential for future applications to hydraulic phenomena at prototype scale.